Key predistribution with location and time binding:novel approach against node replication attacks in wireless sensor networks - FU Fei; QI Wang-dong (Tongxin xuebao, 2010)
A novel pairwise key predistribution approach called LTB （location and time binding） was proposed ,in which the key material of each node were bounded with its original deployment location and time so that each node could establish pairwise keys with its neighbors only at its original deployment location. Since replicas were deployed at different locations other than the original,they could not be accepted by their neighbors. LTB eliminates node replication threats completely while its communications overhead is much lower than that of periodical detection approaches with O（n） against O（pn3/2）,in which p is the number of detection periods and n is the number of nodes in the network.